Trust in Nurses Scale: validation of the core elements. Issue 2 (14th July 2020) - Comparcini, Dania; Simonetti, Valentina; Tomietto, Marco; Radwin, Laurel E.; Cicolini, Giancarlo
Abstract : Background: The Trust in Nurses Scale (TNS) was developed and psychometrically assessed so that patients' trust could be accurately and reliably measured. The TNS has been translated, assessed and administered to patients in Europe, Asia and North America. Aim: This descriptive, cross‐sectional, correlational study aimed to assess the psychometric characteristics of the Italian version of the Trust in Nurses Scale. Methods: An Italian version of the TNS was developed. We used a forward–backward translation methodology to establish semantic and conceptual equivalence within the Italian context. The scale was then administered to a convenience sample of 200 hospitalised patients in medical, surgical or oncology units. Internal consistency and construct validity were assessed performing Cronbach's alpha and confirmatory factor analysis (CFA). Both a 4‐item and a 5‐item TNS were assessed. Results: The 4‐item TNS demonstrated better construct validity than the 5‐item version. Similarly, the internal consistency reliability was better with 4 items than 5 (0.83 and 0.79, respectively). Conclusion: The Italian version of the scale has acceptable reliability and validity and may be used to assess this aspect of the nurse–patient relationship. Being tested in different settings, it may be used with all patients admitted to hospital. Trust in nurses is critically important to patient outcomes; however, it is rarely measured quantitatively on a wide scale. The use of the Italian validated scale could be useful to increase evidences on this important topic, as it represents a core component of nursing care.